2016
DOI: 10.1111/ina.12290
|View full text |Cite
|
Sign up to set email alerts
|

Potentially harmful secondary metabolites produced by indoorChaetomiumspecies on artificially and naturally contaminated building materials

Abstract: The presence of the fungal genus Chaetomium and its secondary metabolites in indoor environments is suspected to have a negative impact on human health and well-being. About 200 metabolites have been currently described from Chaetomium spp., but only the bioactive compound group, chaetoglobosins, have been screened for and thus detected in buildings. In this study, we used a liquid chromatography high-resolution mass spectrometry approach to screen both artificially and naturally infected building materials fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Chaetomium spp., together with several other genera such as Stachybotrys , Aspergillus and Penicillium , are of concern because of their ability to grow in the indoor environment and their association with production of bioactive metabolites (Brasel et al., 2005, Samson et al., 2010, Andersen et al., 2016, Došen et al., 2016). Depending on the type of water damaged building material, Chaetomium sensu lato are found in 16–66 % of environmental samples (Flannigan and Miller, 2011, Andersen et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaetomium spp., together with several other genera such as Stachybotrys , Aspergillus and Penicillium , are of concern because of their ability to grow in the indoor environment and their association with production of bioactive metabolites (Brasel et al., 2005, Samson et al., 2010, Andersen et al., 2016, Došen et al., 2016). Depending on the type of water damaged building material, Chaetomium sensu lato are found in 16–66 % of environmental samples (Flannigan and Miller, 2011, Andersen et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…All samples were further analysed for peaks not detected by the previous approach, and those were matched against Antibase2012 for a tentative identification. Metabolites that did not match were considered as novel compounds and their elemental composition was determined from the accurate mass (±2 ppm) and isotopic pattern (Kildgård et al., 2014, Došen et al., 2016). The peak areas of [M+H] + , [M+Na] + or [M+H 2 O] + of all the compounds, including the tentatively identified and the novel compounds, were then integrated in the Agilent MassHunter Quant software using extracted ion chromatograms ±12 ppm and the peak areas for multivariate data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…elatus (closely related to Ch. rectangulare); collectively, they represent 70% of the 145 isolates [2,3,9]. These studies showed that, although the members of the Ch.…”
Section: Introductionmentioning
confidence: 96%
“…Metabolite profiling of extracts of pure cultures, biomass and dust samples collected in the water-damaged kindergarten was performed using ultra-high performance liquid chromatography-diode array detection-quadrupole time-of-flight mass spectrometry (UHPLC-DAD-QTOFMS) as described by Dosen et al [ 39 ] using an Agilent Infinity 1290 UHPLC system (Agilent Technologies, Santa Clara, CA, USA) coupled to an Agilent 6545 QTOF MS equipped with a Dual Jet Stream electrospray ion source. The system was equipped with a diode array detector scanning in the range 200–640 nm 20 times/s [ 36 ].…”
Section: Methodsmentioning
confidence: 99%